The Choephori of Aeschylus - Verrall, A. W.; Aeschylus (London : Macmillan, 1983)
The City Center of Music & Drama Inc. in association with the Greek Theatre Association (Los Angeles), James A. Doolittle, director presents Greek Tragedy Theatre, Piraokon Theatron, founder-producer-director: Dimitrios Rondiris, producer: Theodore Kritas, Aeschylus' "Choephori" and "Eumenides" tragedies. Translation: J. Gryparis, direction: D. Rondiris, choreography: Loukia, music: K. Kydoniatis.
Includes index.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Orestes (Greek mythology) -- Drama; Theater programs -- New York (State) -- New York; Theater programs -- 1961.